The Structure and Meaning of Poetry in Poetry Compilation of Kata Kota as the Primary School Teaching Materials - Suaidah, Suaidah; Nuryatin, Agus; Doyin, Mukh (Universitas Negeri Semarang, 2022)
Poetry is important to instill values and develop aesthetic awareness from figurative language play. In this research, the researchers used the poetry compilation of Kata Kota as the primary school teaching material alternative. This research aims to (1) find out the poetic structure of the poetry compilation of Kata Kota by Kudus - Fiction Community, (2) determine the meaning of the poetry in the poetry compilation, (3) determine the reliability of the poetry from the poetry compilation as the primary school teaching material alternative based on the structure and meaning. This pragmatic research approach collected the data via a literature study. Then, the researchers analyzed the data with the hermeneutic reading technique. The discussion about the poetic structure and the meaning of 15 poetry found nine of them were reliable to use as the primary school teaching material alternative. The other six pieces of poetry were not reliable for primary school teaching material alternatives. The research results contribute to the literature study development, especially in dealing with poetry. This research can be the object for other younger writers to read more qualified literature works and to write qualified literature works.